Revealing Trust in International Fashion Brands in the Digital Era - Kesumahati, Erilia; Viorilla, Princesscia Vanessa; Yuwono, Wisnu (Universitas Batanghari Jambi, 2026)
This study aims to analyze the influence of Celebrity Endorser, e-WOM, Brand Awareness, Brand Image, Brand Love on Trust. This study uses a quantitative approach with a survey method on 329 respondents who are social media users and buyers of international fashion brands. The data analysis techniques used are SEM and SmartPLS. The results of this study found that there is a proven hypothesis in this study, namely the Celebrity Endorser variable has a significant direct influence on the e-WOM variable, and the E-WOM, Brand Image, and Brand Love variables have a significant direct influence on the Trust variable. However, the Celebrity Endorser and Brand Awareness variables do not have a direct influence on the Trust variable. This finding shows the importance of the role of e-WOM, brand image, and brand love in fostering trust in international fashion brands.